2021
DOI: 10.1029/2020ja029024
|View full text |Cite
|
Sign up to set email alerts
|

ULF Wave Driven Radial Diffusion During Geomagnetic Storms: A Statistical Analysis of Van Allen Probes Observations

Abstract: Earth's inner magnetosphere is host to a population of highly variable, highly dynamic, and highly energetic particles known as the Van Allen radiation belts (Li & Hudson, 2019;Van Allen et al., 1958, 1959. Of particular interest is the outer radiation belt population that typically occupies radial distances greater than 3-4 R E and is host to extremely energetic MeV electrons. During geomagnetic storms, this population undergoes dramatic enhancements as well as rapid flux dropouts (e.g., Baker et al., 2004;Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 122 publications
(246 reference statements)
9
60
0
Order By: Relevance
“…The statistical and event study analysis confirms some expected and previously observed features of externally driven compressional ULF wave propagation in the inner magnetosphere during geomagnetic storms, and also demonstrates the importance of phenomena that has received comparatively less attention. In direct agreement with previous results (e.g., Sandhu, Rae, Wygant, et al, 2021;Simms et al, 2010), we report significant enhancements in ULF wave power during the main phase of geomagnetic storms, associated with elevated solar wind conditions and a high level of solar wind -magnetosphere coupling. The main phase enhancements occur across all observed L values, with larger enhancements at higher L values.…”
Section: Interpretation and Concluding Remarkssupporting
confidence: 93%
See 4 more Smart Citations
“…The statistical and event study analysis confirms some expected and previously observed features of externally driven compressional ULF wave propagation in the inner magnetosphere during geomagnetic storms, and also demonstrates the importance of phenomena that has received comparatively less attention. In direct agreement with previous results (e.g., Sandhu, Rae, Wygant, et al, 2021;Simms et al, 2010), we report significant enhancements in ULF wave power during the main phase of geomagnetic storms, associated with elevated solar wind conditions and a high level of solar wind -magnetosphere coupling. The main phase enhancements occur across all observed L values, with larger enhancements at higher L values.…”
Section: Interpretation and Concluding Remarkssupporting
confidence: 93%
“…Overall, these results have significant implications for our understanding of storm time ULF wave dynamics, particularly efforts to model the magnitude of ULF wave driven radial diffusion during active periods (e.g., Brautigam & Albert, 2000;Ozeke et al, 2014;Sandhu, Rae, Wygant, et al, 2021). We demonstrate that parameterization by the L value alone is comparatively inadequate in describing the radial variation of wave power during active periods.…”
Section: Interpretation and Concluding Remarksmentioning
confidence: 82%
See 3 more Smart Citations